Atraumatic Restoration of Vertical Food Impaction with an Open Contact Using Flowable Composite Resin Aided by Cerclage Wire under Tension. (7th August 2016) - Li, Quan-Li; Ying Cao, Chris; Xu, Qiang-Jian; Xu, Xiao-Hua; Yin, Jia-Li
Abstract : To date, treating vertical food impaction with open contact effectively, especially with an atraumatic therapy, remains a challenge. In this study, we developed a simple, atraumatic, and economic therapeutic measure to treat vertical food impaction. The scientific rationale of our therapeutic technique is to restore an intact and firm proximal contact with proper location and form relationships to prevent forceful interproximal wedging of food, which in turn protects interdental papilla. We performed the procedure using flowable composite resin or composite resin cement with the aid of a cerclage wire under tension to rebuild the contact area. The reported method is especially useful for some challenging clinical cases, such as food impaction after crown and inlay on onlay restoration, and some conventional treatment methods, such as contouring the marginal ridge and developmental grooves, are ineffective.